Penerapan Metode Technology Acceptance Model untuk Pengukuran Tingkat Penerimaan Aplikasi SIM3LON - Adila Safitri; Ni’mah Akbar Habibie; Illyin Almeito; Moh. Hasyimi; Yonathan Saputra; Eko Sediyono; Aris Puji Widodo (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
This research was conducted to test user acceptance (agent and base) of SIM3LON system using Technology Acceptance Model (TAM). This test was done by measuring the influence of variable Perceived Ease of Use, Perceived Usefulness and Intention to use with a likert value of 1-5 with TAM method. The testing method is done using the R GUI tool to generate validity and reliability values and perform calculations using the "product moment correlation" method. The data was obtained through a questionnaire distributed to respondents PT Catur Karya agent and the base. This study resulted in an average validity value of 0.77 which means agents and bases feel SIM3LON is easy to use, while the reliability value is 0.72 which means agents and bases feel this SIM3LON system benefits in the work.